Surface chemistry of dihydromyrcenol (2,6-dimethyl-7-octen-2-ol) with ozone on silanized glass, glass, and vinyl flooring tiles - Ham, Jason E.; Raymond Wells, J. (Atmospheric environment (1994), 2009)
The surface-phase reaction products of dihydromyrcenol (2,6-dimethyl-7-octen-2-ol) with ozone (O 3), air, or nitrogen (N 2) on silanized glass, glass and vinyl flooring tile were investigated using the recently published FACS (FLEC (Field and Laboratory Emission Cell) Automation and Control System). The FACS was used to deliver ozone (100 ppb), air, or N 2 to the surface at a specified flow rate (300 mL min −1) and relative humidity (50%) after application of a 2.0% dihydromyrcenol solution in methanol. Oxidation products were detected using the derivatization agents: O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine hydrochloride (PFBHA) and N, O-bis(trimethysilyl)trifluoroacetamide (BSTFA). The positively identified reaction products were glycolaldehyde, 2,6-dimethyl-5-heptenal, and glyoxal. The proposed oxidation products based on previously published VOC/O 3 reaction mechanisms were: 2,6-dimethyl-4-heptenal, 6-methyl-7-octen-2-one and the surface-specific reaction products: 6-methyl-6-hepten-2-one, 6-methyl-5-hepten-2-one, and 6-hydroxy-6-methylheptan-2-one. Though similar products were observed in gas-phase dihydromyrcenol/O 3 reactions, the ratio, based on peak area, of the reaction products was different suggesting stabilization of larger molecular weight species by the surface. Emission profiles of these oxidation products over 72 h are also reported.